2016
DOI: 10.1016/j.foodchem.2016.05.182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hofmeister salt series on gluten network formation: Part I. Cation series

Abstract: Different cationic salts were used to investigate the effects of the Hofmeister salt series on gluten network formation. The effects of cationic salts on wheat flour dough mixing properties, the rheological and the chemical properties of the gluten extracted from the dough with different respective salts, were investigated. The specific influence of different cationic salts on the gluten structure formation during dough mixing, compared to the sodium ion, were determined. The effects of different cations on do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…These results are in agreement with those obtained by (Tuhumury, 2016) which found that by MgCl 2 addition in wheat flour the dough development time decreased. Also, (Sehn, 2015) obtained similar results at low levels of magnesium sulfate salt addition when DT decrease and at high levels increase.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in agreement with those obtained by (Tuhumury, 2016) which found that by MgCl 2 addition in wheat flour the dough development time decreased. Also, (Sehn, 2015) obtained similar results at low levels of magnesium sulfate salt addition when DT decrease and at high levels increase.…”
Section: Resultssupporting
confidence: 93%
“…The dough stability results indicated the fact that the magnesium lactate salt addition was less effective at maintaining the stability of the dough samples, at low levels these results being in agreement with those obtained by (Tuhumury et al, 2016). This may be due to the fact the magnesium ions are water structure breakers and may destabilize folded proteins (Sehn, 2015) conducting to low stability values.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…However, when salt is added in wheat flour dough, both ions interact with chemical groups of the gluten proteins. According to Tuhumury et al (2016), the effect of anion salt compared to the cation one on gluten structure is higher, probably due to the anion ability to bind more effectively with proteins and screening of the electrostatic repulsion on specific binding sites. This explains the high amount of anion from lactate salts present in wheat flour dough, which increased its stability.…”
Section: Resultsmentioning
confidence: 99%
“…The calcium carbonate and calcium citrate are the most common calcium salts used (Abrams et al, 1991) but also other forms like calcium lactate, calcium chloride, calcium phosphate, calcium propionate, calcium gluconate are very used due to their preservation effect on food products (Martín-Diana et al, 2007). The effect of calcium ions from different sources on dough rheological properties was investigated by different researchers (Kaur, Bala, Singh, & Rehal, 2011;Morita, Nakamura, Hamauzu, & Toyosawa, 1994, 1996Salovara, 1982;Sehn, Nogueira, Almeida, Chang, & Steel, 2015;Tuhumury, Small, & Day, 2016). According to those authors, it seems that, in general, the calcium ions addition in wheat flour presented a weakening effect on dough physical properties.…”
Section: Introductionmentioning
confidence: 99%